STUDENTS` PERCEPTION ON PROGRAM SPECIFICATION OF ELT CURRICULUM BASED ON AUN-QA CRITERIA - Elsa Rahmi; Refnaldi Refnaldi; Fitrawati Fitrawati (Journal of English Language Teaching, 2018)
English Language Teaching Program is one of the programs at UNP that will propose to be certified by ASEAN University Network Quality Assurance (AUN-QA). One of the requirements proposed by AUN-QA is getting feedback from stakeholders on curriculum. Program Specification is one of one crucial feature in curriculum. This study aimed to find out the students` perception on program specification of English Language Teaching Program based on AUN-QA criteria and to find what improvement needed based on students` perception. This survey study involved students first year, second year, third year and fourth year of ELT Program at UNP. Questionnaire containing 15 items was distributed to 352 students through Google form in order to get the data. Questionnaire consist four scales and then weighing is done in order to convert it into mean score. Then, the mean scores were converted into degree of perception. It is found out that the mean score for program identity is very high, 3.22 and it means that students have very good perception toward program identity. The mean score for potential career is also very high, 3.38 and indicates that students have very good perception toward potential career. The main finding shows that students have very good perception toward program specification even though there are few comments given by them who gave negative response on questionnaire. However, there is a little improvement needed based on students` perception. In conclusion, there is slighly improvement needed based on students` perception.Key words: Perception, Program Specification, AUN-QA